Indigenous Legal Issues, Indigenous Perspectives and Indigenous Law in the New Zealand LLB Curriculum - Carwyn Jones (Legal Education Review)
The article proposes a method of teaching Administrative Law that engages with the historical and political impact of administrative decisions on Indigenous peoples and their cultures while still addressing the traditional doctrinal concerns of an Administrative Law course. The article begins by explaining what it understands by the concept of an ‘Indigenous perspective’, and identifying how such perspectives can be incorporated into a law degree. It then outlines the potential role of Administrative Law as a vehicle for incorporating an Indigenous perspective, explaining the pedagogical benefits of expanding Administrative Law courses in this way